PERTANGGUNGJAWABAN PIDANA KORPORASI PELAKU TINDAK PIDANA PEMBAKARAN HUTAN DAN LAHAN UNTUK KEPENTINGAN PERKEBUNAN SAWIT DI INDONESIA - Sopiyanto, Sopiyanto; Chandra, Tofik Yanuar; Ismed, Mohamad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The background of the problem in this study is where forest and land burning, especially for the interests of palm oil plantations in Indonesia, is a disaster that can harm and endanger human life and the sustainability of the existing ecosystem, law enforcement is considered ineffective against corporations as perpetrators of forest and land burning crimes so that improvements need to be made. The Indonesian Criminal Code has not regulated sanctions against corporations that commit forest and land burning crimes, so that special laws relating to the environment can be applied. The problem in this study is how to enforce the law against perpetrators of forest and land burning crimes and how to be held criminally responsible for corporations that commit forest and land burning crimes. The theories used in this study are First, the theory of Criminal Responsibility and the second is the theory of Law Enforcement according to Lawrence M. Friedman. The results of this study are that the evidence to ensnare a Corporation as a suspect can use the theory of absolute liability, the theory of vicarious liability, the theory of identification. And law enforcement against corporations committing forest and land burning crimes in Indonesia is considered ineffective, this is due to the weakness of the law enforcement apparatus itself consisting of the Police, Prosecutors and Courts so that improvements are needed both in terms of quantity and quality